Dhanya janma jāhalā : Śrímatī Hirābāī Baḍodekara yāñce jīvanagāṇe - Humaṇe, Rājārāma (Śrīvidyā Prakāśana, 1980)
On the life and achievements of Hirābāī Baḍodekara, b. 1905, Marathi classical vocalist of the Hindustani style of music.